Rational drug design and biochemical analysis in the development of targeted therapies against Malignant Pleural Mesothelioma - Price, Trevor T. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Malignant Pleural Mesothelioma (MPM) is a fatal neoplasm arising from cells of the esothelial lining of the pleural cavity and associated with prolonged exposure to asbestos. This highly resistant malignancy is largely unresponsive to conventional chemotherapy and while promising novel treatment strategies are under investigation, to date no truly effective clinical solutions have been discovered. In this study, a rational drug design approach was undertaken to develop and biochemically evaluate novel targeted agents for the treatment of MPM.
Embargo End Date: 2020-07-01
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin, 2012